(3GdeaQOGJ GdWHjIs
(3ChdgG (B:s
(3JHOG HMQa GdHGH HQTG hTGf , hgh MTjTI ObjbI efHJgG MjGV GdeGA hGdTWhW hOGNd GdBHGQ , JTHg fHGJ GdcRHQI s
(3BNQgG (B:s
(3eHQO HGdJdL hjUH Ydi QCSg HGdKdL Jbhje s
(3GdfSNI HgG MhGTs
(3bWYI eQJHI Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B178 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs